1999
DOI: 10.1620/tjem.187.311
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alcohol Dehydrogenase 2 and Aldehyde Dehydrogenase 2 Genotypes in Alcohol-Induced Vasospasic Angina.

Abstract: Alcohol ingestion often provokes attacks in patients with vasospastic angina. Type 2 aldehyde dehydrogenase (ALDH2) deficiency, which is based on a single point mutation (Glu487Lys) of the ALDH2 gene, is common in the Japanese population, but rare among the Caucasian population. We investigated how the genotype of ALDH2 affects the characteristics of alcohol-induced vasospastic angina. Ninety-one patients with vasospastic angina who had ingested alcohol daily or occasionally were studied. Patients had been dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…9 We and others also reported that CSA was induced by alcohol drinking, particularly in those with AFS. 10,11 The present study demonstrates for the first time that the frequencies of the variant ALDH2*2 genotype and AFS are significantly higher in the CSA group than in the non-CSA group. Conversely, the frequencies of CSA and AFS were significantly higher in the variant ALDH2*2 group than in the wild ALDH2*1*1 group.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…9 We and others also reported that CSA was induced by alcohol drinking, particularly in those with AFS. 10,11 The present study demonstrates for the first time that the frequencies of the variant ALDH2*2 genotype and AFS are significantly higher in the CSA group than in the non-CSA group. Conversely, the frequencies of CSA and AFS were significantly higher in the variant ALDH2*2 group than in the wild ALDH2*1*1 group.…”
Section: Discussionsupporting
confidence: 48%
“…9 We and others have reported that CSA can be induced by alcohol ingestion, particularly in those with AFS. 10,11 However, the relationships of CSA with ADH1B and ALDH2 gene polymorphisms remain to be elucidated. In the present study, we investigated the association of polymorphisms of ADH1B and ALDH2 with CSA.…”
Section: Clinical Perspective On P 1673mentioning
confidence: 99%
“…About half of East Asians show rapid and intense alcohol flushing after drinking alcohol in the amount that has no effect on Caucasians (6-8). We and others have shown that CSA could be induced by alcohol ingestion (9)(10)(11).…”
Section: Discussionmentioning
confidence: 82%
“…East Asians have been shown to have a mutation of the ALDH2*2 gene that leads to a reduced activity and intolerance to alcohol (ethanol) ingestion in about half of the population (5)(6)(7)(8). We and others have reported that CSA is induced by alcohol ingestion, particularly in those who have alcohol flushing upon alcohol intake (9)(10)(11). However, the relationship between alcohol intake and CSA has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…People carrying the mutations have a low tolerability to alcohol and are at higher risk of developing cardiovascular diseases and of elevated blood pressure. [ 7 8 ]…”
Section: Introductionmentioning
confidence: 99%